Deletions or duplications in KCNQ2 can cause benign familial neonatal seizures. Issue 12 (3rd August 2007) - Heron, S E; Cox, K; Grinton, B E; Zuberi, S M; Kivity, S; Afawi, Z; Straussberg, R; Berkovic, S F; Scheffer, I E; Mulley, J C
Abstract : Background: Benign familial neonatal seizures are most often caused by mutations in the voltage-gated potassium channel subunit gene KCNQ2 . More than 60 mutations have been described in BFNS families, approximately half of which lead to protein truncation. The hypothesis of this study was that deletion or duplication of ⩾1 exons of KCNQ2 could cause BFNS in cases without coding or splicing mutations. Methods: Multiplex ligation-dependent probe amplification (MLPA) was used to test a group of 21 unrelated patients with clinical features consistent with either BFNS, benign familial neonatal–infantile seizures or sporadic neonatal seizures, for exonic deletions and duplications. Results: Three deletions and one duplication mutation were identified in four familial cases and cascade testing of their available family members showed that the mutations segregated with the phenotype in each family. The junction fragment for one of the deletions was amplified by PCR and sequenced to characterise the breakpoint and verify that a deletion had occurred. Conclusions: Submicroscopic deletions or duplications of KCNQ2 are seen in a significant proportion of BFNS families: four of nine (44%) cases previously testing negative for coding or splice site mutation by sequencing KCNQ2 and KCNQ3 . MLPA is an efficient second-tier testing strategy for KCNQ2 to identify pathogenic intragenic mutations not detectable by conventional DNA sequencing methods.